Peat deposit as base object for reconstruction of the condition of environment. Methodical aspects for regions with the continental climate; ENVIROMIS' 2006 - Preis Yu. I.; Antropova N. A. Natalya Alexeevna; Bobrov V. A.; Orlova L. A.; Sharapova T. A. (2006, 2006)
В фонде НТБ ТПУ отсутствует